ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 MENGENAI ANAK LUAR KAWIN PERSPEKTIF UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK DAN HUKUM ISLAM - Megawati, Megawati (UIN Fatmawati Sukarno Bengkulu, 2017)
After the issuance of the decision of the Constitutional Court Number 46/PUU-VIII/2010, Article 43 of Law Number 1Year 1974 concerning Marriage which originally stated that the married child has only a civil relationship with his mother and his mother’s family, has blood relation including civil relationship with father his biological and his father’s family although there must be recognition or can be proven on the basis of science and technology and/or other evidence. The decision of the Constitutional Court can be seen from two sides, namely the protection of the rights of the married child, and the conformity of the understanding of the child outside of marriage according to Islamic law, because according to Islamic law the child outside marriage should not at all have a nasab relationship with his biological father. Based on the above background, this research reveals two issues, firstly how the legal power of the Constitutional Court decision regarding the outsider marriage perspective of Law Number 35 year 2014 on Child Protection. Second, what is the conformity between the Constitutional Court decision No. 46/PUU-VIII/2010 concerning the married child against the provision of an outsider from the perspective of Islamic law. This type of research is normative juridical research or library research which is then described descriptively. The results of this study conclude that the legal force of the Constitutional Court decision is binding (final and binding). Recognition of the rights of children outside marriage shall be exercised by all parties concerned, in accordance with Article 59 paragraph 2 letter o Law No. 35 of 2014 on Child Protection, that every child has the right to survival, growth and development and is entitled to protection from violence and discrimination, including special protection to children who are victims of stigmatization from labeling related to the condition of their parents. Meanwhile, if you look at the provisions in Islamic law, the decision of this Constitutional Court should be adjusted to the understanding of children outside marriage in Islamic law, because the Constitutional Court decision is a law made man, while Islamic law is a law that comes from Allah SWT. It is also important to revise Article 2 paragraph (2) on the provision of marriage registration as a legal marriage requirement to be only an administrative requirement. “Outer Child Marriage, Constitutional Court and Islamic Law”.